2005
DOI: 10.5993/ajhb.29.4.6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sex-specific Normative Beliefs in Undergraduate Alcohol Use

Abstract: Pre-weekend goals to limit drinking predicts fewer weekend binge episodes among young adults with problem drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
27
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 0 publications
12
27
1
Order By: Relevance
“…This is similar to the misperceptions found at analogous American colleges (e.g. Thombs et al 2005), which is of interest given the legal and cultural differences between the two countries (Delk and Meilman 1996).…”
Section: Social Norms Research Outside Of the Usasupporting
confidence: 63%
“…This is similar to the misperceptions found at analogous American colleges (e.g. Thombs et al 2005), which is of interest given the legal and cultural differences between the two countries (Delk and Meilman 1996).…”
Section: Social Norms Research Outside Of the Usasupporting
confidence: 63%
“…Emails with the same information were sent at follow-up. The response rate was 66%, which is consistent with other web-delivered approaches with college populations (Larimer et al, 2007;McCabe et al, 2005;Thombs et al, 2005). Assessments were collected at two time points: (a) baseline (during the summer before college matriculation) and (b) follow-up (during the fall of the second year of college [15 months later]).…”
Section: Recruitment and Proceduresmentioning
confidence: 80%
“…It is also possible that, along with composition changes, same-gender peer drinking becomes more salient over time. Indeed, it has been found that same-sex peer norms have a greater infl uence on drinking behavior than opposite-sex peers (Lewis and Neighbors, 2004;Thombs et al, 2005). Therefore, men may be attending to the norms of their male peers, whereas women are attending to those of their female peers, and this may become stronger over time.…”
Section: Discussionmentioning
confidence: 99%